Nano-silver colloid and preparation method thereof
By using copper-lanthanum alloy and liquid nitrile rubber in nano-silver rubber to form an interpenetrating network polymer structure, the stability and compatibility problems of nano-silver rubber at high temperatures are solved, and the demand for high-performance conductive materials is achieved.
Patent Information
- Application Number
- CN202411911155.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
Existing nano silver glues tend to cause silver layer to detach and oxidize copper particles at high temperatures, and the compatibility between silver powder and copper powder is not ideal, affecting the conductivity and stability.
Through formulation adjustment, composite silver powder filler contains copper-lanthanum alloy and liquid nitrile rubber is added to the resin to form an interpenetrating network polymer structure to improve the uniform distribution and binding force of silver powder and copper-lanthanum alloy.
It significantly improves the stability and mechanical properties of nano silver glue, maintains conductivity and shear strength, and performs well in flexural resistance tests, and has a low resistance change rate.
Smart Images

Figure BDA0005205694100000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silver paste, in particular to a nano silver paste and a preparation method thereof. Background Art
[0002] Nano silver glue is an adhesive that uses nano-scale silver particles as conductive fillers. Through the bonding effect of the resin matrix, a high-density conductive network is formed to achieve efficient conductive connection. This material has high electrical and thermal conductivity and is suitable for electronics, optoelectronics, communications and other fields.
[0003] Nano silver particles are small in size and prone to agglomeration or migration, thus affecting the uniformity and conductivity of the conductive adhesive. Prior art research has found that adding copper can improve the mechanical properties of silver adhesive, but copper is easily oxidized, so it is usually necessary to prepare silver-coated copper. This process requires high coating technology, uneven coating, poor density, and difficult to solve the problems of particle size control and dispersibility.
[0004] Studies have shown that silver-coated copper powder exhibits good dispersibility and antioxidant properties in conductive adhesives. However, due to the different melting points and hardness of silver and copper, the silver layer may detach from the surface of the copper powder at high temperatures, causing the copper particles to be exposed and rapidly oxidized. The compatibility of silver powder and copper powder in conductive adhesives is not completely ideal. Although the oxidation resistance and conductivity of copper powder can be improved to a certain extent through the preparation of silver-coated copper powder, its stability and bonding strength still need to be further optimized. Summary of the invention
[0005] The present invention overcomes the above technical problems and thus provides a nano silver paste and a preparation method thereof, wherein the nano silver paste can maintain electrical conductivity and shear strength while also exhibiting good stability. By adjusting the formula, the present invention significantly improves the stability of the silver paste without reducing electrical conductivity and shear strength, thereby meeting the demand of the electronics industry for high-performance conductive materials.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] The invention discloses a nano silver paste, comprising the following raw materials in parts by weight: 80 parts of composite silver powder filler, 5 to 15 parts of resin, 3 to 7 parts of liquid nitrile rubber, 1 to 4 parts of organic carrier, 0.1 to 0.5 parts of defoamer, and 2 to 6 parts of diluent; preferably, the nano silver paste comprises the following raw materials in parts by weight: 80 parts of composite silver powder filler, 8 to 13 parts of resin, 4 to 6 parts of liquid nitrile rubber, 1 to 3 parts of organic carrier, 0.1 to 0.5 parts of defoamer, and 2 to 6 parts of diluent;
[0008] The composite silver powder filler comprises the following raw materials in parts by mass: 100 parts of silver powder and 2 to 10 parts of copper-lanthanum alloy; preferably, the composite silver powder filler comprises the following raw materials in parts by mass: 100 parts of silver powder and 5 to 8 parts of copper-lanthanum alloy.
[0009] According to some preferred embodiments, the silver powder is spherical particles.
[0010] According to some preferred embodiments, the D50 of the silver powder is 300-600 nm, preferably, the D50 of the silver powder is 300-500 nm.
[0011] According to some preferred embodiments, the copper-lanthanum alloy includes the following mass percentage elements: 5-10wt% La; preferably, the copper-lanthanum alloy is composed of the following mass percentage elements: 5-10wt% La, and the balance is Cu; more preferably, the copper-lanthanum alloy is composed of the following mass percentage elements: 5-8wt% La, and the balance is Cu.
[0012] Among them, copper-lanthanum alloy has excellent electrical conductivity due to its fine crystal structure and dense organization, which plays an important role in improving the comprehensive performance of composite silver powder filler. The introduction of lanthanum can enhance the electrical conductivity and thermal conductivity of the copper matrix, while improving the oxidation resistance of copper; in addition, copper alloy containing lanthanum can improve the mechanical properties of silver glue, including tensile strength, shear strength, elongation and toughness.
[0013] According to some preferred embodiments, the resin is bisphenol A epoxy resin and novolac epoxy resin.
[0014] Preferably, the phenolic epoxy resin is o-cresol epoxy resin.
[0015] According to some preferred embodiments, the resin includes 70 to 80 parts by mass of bisphenol A epoxy resin and 10 to 30 parts by mass of novolac epoxy resin.
[0016] According to some preferred embodiments, the viscosity of the liquid nitrile rubber is 15-25 Pa·s.
[0017] According to some preferred embodiments, the liquid nitrile rubber has a bound acrylonitrile content of 26-28%.
[0018] Among them, liquid nitrile rubber and resin form an interpenetrating network polymer structure through cross-linking reaction, which gives the silver glue excellent adhesion. Due to the active chemical properties of liquid nitrile rubber, it is easy to combine with metal to form a silver layer on the surface of copper-lanthanum alloy powder. In addition, liquid nitrile rubber, as an effective cross-linking agent, also enables the silver powder to be evenly dispersed between the resins.
[0019] According to some preferred embodiments, the organic carrier is at least one of polyvinyl alcohol, polyvinyl butyral, paraffin and ethyl cellulose.
[0020] According to some preferred embodiments, the diluent is at least one of terpineol, ester alcohol, tributyl citrate and cyclohexylisoborneol.
[0021] According to some preferred embodiments, the shear strength of the nano silver paste is greater than 55 MPa, preferably 57-65 MPa.
[0022] According to some preferred embodiments, the volume resistivity of the nano silver paste is 5×10 -6 ~6×10 -6 Ω·cm, preferably 5.2×10 -6 ~5.6×10 -6 Ω·cm.
[0023] The present invention also discloses a method for preparing nano silver colloid, comprising the following steps:
[0024] S1. Mix the resin, diluent, liquid nitrile rubber, organic carrier and composite silver powder filler according to the required ratio to obtain a first mixture
[0025] S2. Add a defoaming agent to the first mixture, stir, and filter to obtain nano silver colloid.
[0026] In S1, the mixing is performed using a high-speed disperser.
[0027] In S1, the mixing speed is 1000-1500 rpm.
[0028] In S1, the mixing time is 2 to 10 minutes.
[0029] In S2, the mesh number of the filtration is 400-500 meshes.
[0030] The preparation method of the nano silver paste of the present invention also includes a preparation method of a composite silver powder filler;
[0031] The preparation method of the composite silver powder filler comprises the following steps:
[0032] Step 1. crushing, grinding and sieving the copper-lanthanum alloy to obtain copper-lanthanum alloy powder;
[0033] Step 2. Mix the copper-lanthanum alloy powder and the silver powder to obtain a composite silver powder filler.
[0034] In step 1, the grinding is performed using a ball mill.
[0035] In step 1, the particle size of the copper-lanthanum alloy powder after screening is D50=1-5 μm
[0036] The sintering procedure of the nano silver paste of the present invention is sintering at 80-120° C. for 20-30 minutes and then sintering at 200-220° C. for 30-50 minutes.
[0037] The sintering method of the nano silver paste of the present invention is pressureless sintering.
[0038] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] 1. The present invention relates to a nano silver paste formula, wherein the composite silver powder filler is specially proportioned with copper-lanthanum alloy powder. This proportioning utilizes the excellent dispersibility of copper-lanthanum alloy powder to effectively improve the stability and mechanical properties of the silver paste. In the formula, liquid nitrile rubber is added to the resin, which not only enhances the adhesion of the silver paste due to the interpenetrating network polymer structure formed by it and the resin, but also because of its active chemical properties, the liquid nitrile rubber has good bonding with the metal powder, further promoting the uniform distribution of the silver powder and the copper-lanthanum alloy powder in the resin matrix. This uniform distribution is crucial for improving the overall performance of the silver paste. Therefore, through these improvements, the nano silver paste of the present invention exhibits good mechanical properties, as well as excellent stability and durability.
[0041] 2. Due to the adjustment of the above formula, the nano silver glue of the present invention not only maintains the conductivity and shear strength, but also enhances its stability. After three bends, the simulation device was tested for anti-bending performance, and the results showed excellent performance, with a resistance change rate of only 2.3% to 7.7%. DETAILED DESCRIPTION
[0042] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0043] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0044] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60-120 and 80-110 is listed for a specific parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0047] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0048] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0049] If not specifically stated, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0050] The raw material information used in the following examples is as follows:
[0051] The bisphenol A epoxy resin is Nan Ya bisphenol A epoxy resin NPEL-128; its epoxy equivalent is 180-190 g / eq, and its viscosity (25° C.) is 11000-15000 cps.
[0052] The phenolic epoxy resin is CNE-202 o-cresol epoxy resin from Changchun, Taiwan, China; its epoxy equivalent is 180-190 g / eq.
[0053] Spherical silver powder is from Laiwu Dada Alloy Co., Ltd.; its D50 is 300nm, and its specific surface area is 1.03m 2 / g.
[0054] The copper-lanthanum alloy was purchased from Changsha Wante New Materials Co., Ltd.; its content: 90wt% Cu, 10wt% La.
[0055] Liquid nitrile rubber was purchased from Hengshui Ruien Rubber & Plastic Technology Co., Ltd. (XL2740); its viscosity was 15-25 Pa·s, and the acrylonitrile content of nitrile rubber was 26-28%.
[0056] The defoaming agent is DOWFAX DF103, and the CAS number of its main component is 9082-00-2.
[0057] Ethyl cellulose was purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd. and had a viscosity of 80-120 mPa.s and an ethyl content of 48.5-49.5 wt%.
[0058] Polyvinyl alcohol was purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a degree of alcoholysis of 72.5-74.5 mol and a viscosity of 4.2-5.0 mPa.s.
[0059] Cyclohexylisoborneol was purchased from Shanghai Dingfen Chemical Technology Co., Ltd., CAS No.: 125-12-2.
[0060] Example 1
[0061] 1. The nano silver paste of this embodiment includes the following raw materials by weight: 80 parts of composite silver powder filler, 8 parts of resin, 6 parts of liquid nitrile rubber, 3 parts of organic carrier, 0.3 parts of defoaming agent, and 4 parts of diluent;
[0062] The composite silver powder filler includes the following raw materials in parts by weight: 100 parts of silver powder and 7.5 parts of copper-lanthanum alloy (92 wt % Cu and 8 wt % La).
[0063] In parts by mass, the resin of this embodiment includes 80 parts of bisphenol A epoxy resin (Nan Ya NPEL-128) and 20 parts of novolac epoxy resin (Changchun CNE-202, Taiwan, China).
[0064] The organic carrier in this embodiment is ethyl cellulose.
[0065] The diluent in this embodiment is terpineol.
[0066] 2. The preparation method of the nano silver paste of this embodiment comprises the following steps:
[0067] (1) Prepare the raw materials according to the above formula;
[0068] (2) crushing the copper-lanthanum alloy, ball-milling, and sieving to obtain a copper-lanthanum alloy powder with a D50 of 3.6 μm;
[0069] (3) Mixing the copper-lanthanum alloy powder and the silver powder to obtain a composite silver powder filler;
[0070] (4) mixing the resin, the diluent, the liquid nitrile rubber, the organic carrier and the composite silver powder filler according to the required ratio, using a high-speed disperser for mixing at 1200 rpm for 5 minutes to obtain a first mixture;
[0071] (5) Add defoaming agent to the first mixture and stir for 3 minutes, then filter through a 500-mesh sieve twice to obtain nano silver colloid.
[0072] Example 2
[0073] The following parameters of this embodiment are different from those of Embodiment 1:
[0074] The nano silver paste of this embodiment includes the following raw materials in parts by weight: 80 parts of composite silver powder filler, 13 parts of resin, 4 parts of liquid nitrile rubber, 2.5 parts of organic carrier, 0.5 parts of defoaming agent, and 3 parts of diluent.
[0075] The organic carrier in this embodiment is polyvinyl alcohol.
[0076] The diluent of the present embodiment is cyclohexyl isoborneol ester.
[0077] Other steps and parameters are the same as in Example 1.
[0078] Example 3
[0079] The following parameters of this embodiment are different from those of Embodiment 1:
[0080] The nano silver paste of this embodiment includes the following raw materials in parts by weight: 80 parts of composite silver powder filler, 11 parts of resin, 5 parts of liquid nitrile rubber, 2 parts of organic carrier, 0.1 parts of defoaming agent, and 3 parts of diluent.
[0081] The composite silver powder filler of this embodiment includes the following raw materials in parts by mass: 100 parts of silver powder and 2 parts of copper-lanthanum alloy.
[0082] Other steps and parameters are the same as in Example 1.
[0083] Example 4
[0084] The following parameters of this embodiment are different from those of Embodiment 1:
[0085] The nano silver paste of this embodiment includes the following raw materials in parts by weight: 80 parts of composite silver powder filler, 9 parts of resin, 6 parts of liquid nitrile rubber, 2 parts of organic carrier, 0.5 parts of defoaming agent, and 2.8 parts of diluent.
[0086] In parts by mass, the resin of this embodiment includes 70 parts of bisphenol A epoxy resin and 30 parts of novolac epoxy resin.
[0087] Other steps and parameters are the same as in Example 1.
[0088] Comparative Example 1
[0089] The following parameters of this embodiment are different from those of Embodiment 1:
[0090] The composite silver powder filler in this comparative example includes the following raw materials in parts by mass: 100 parts of silver powder and 10 parts of copper-lanthanum alloy.
[0091] Other steps and parameters are the same as in Example 1.
[0092] Comparative Example 2
[0093] The following parameters of this comparative example are all different from those of Example 1:
[0094] The copper-lanthanum alloy composition in this comparative example is 85 wt % Cu and 15 wt % La.
[0095] Other steps and parameters are the same as in Example 1.
[0096] Comparative Example 3
[0097] The following parameters of this comparative example are all different from those of Example 1:
[0098] The nano silver paste of this embodiment includes the following raw materials in parts by weight: 80 parts of composite silver powder filler, 8 parts of resin, 3 parts of organic carrier, 0.3 parts of defoaming agent, and 4 parts of diluent.
[0099] Other steps and parameters are the same as in Example 1.
[0100] Comparative Example 4
[0101] The following parameters of this comparative example are all different from those of Example 1:
[0102] The nano silver paste of this embodiment includes the following raw materials in parts by weight: 80 parts of composite silver powder filler, 12.8 parts of resin, 1.0 parts of liquid nitrile rubber, 6 parts of organic carrier, 0.3 parts of defoaming agent, and 4 parts of diluent.
[0103] Other steps and parameters are the same as in Example 1.
[0104] Test Example
[0105] 1. Preparation of analog devices:
[0106] The analog device uses a 30mm×30mm copper plate, and prints the low-temperature sintered silver paste prepared in the above embodiments and comparative examples, with a pattern specification of 5mm×5mm square. It is then placed on the silver paste coating with a 3mm×3mm silver-plated chip and bonded together.
[0107] Sintering procedure: heat from 20°C to 100°C and keep warm for 30 minutes, then heat to 210°C and keep warm for 50 minutes to obtain a simulated device.
[0108] 2. Performance test:
[0109] The above analog devices were subjected to performance tests, and the test results are shown in Table 1.
[0110] Table 1
[0111]
[0112] (1) The volume resistivity test is carried out strictly in accordance with the four-wire method, which is achieved by using a high-precision multimeter and a specially designed four-probe test device.
[0113] (2) The shear strength test method refers to T / CASAS 018-2021 "Shear Strength Test Method for Micro-Nano Metal Sintered Connectors".
[0114] (3) The test method for flexural resistance refers to YS / T 606-2023, and the resistance change rate of the tester is measured after bending three times.
[0115] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A nano silver paste, characterized in that: The preparation method comprises the following raw materials in parts by weight: 80 parts of composite silver powder filler, 5 to 15 parts of resin, 3 to 7 parts of liquid nitrile rubber, 1 to 4 parts of organic carrier, 0.1 to 0.5 parts of defoaming agent, and 2 to 6 parts of diluent; The composite silver powder filler comprises the following raw materials in parts by mass: 100 parts of silver powder and 2 to 10 parts of copper-lanthanum alloy.
2. The nano silver paste according to claim 1, characterized in that: The silver powder is spherical particles; And / or, D50 of the silver powder is 300-600 nm.
3. The nano silver paste according to claim 1, characterized in that: The copper-lanthanum alloy includes the following elements in percentage by mass: 5-10 wt % La.
4. The nano silver paste according to claim 1, characterized in that: The resin is bisphenol A epoxy resin and novolac epoxy resin.
5. The nano silver paste according to claim 1, characterized in that: The viscosity of the liquid nitrile rubber is 15 to 25 Pa·s; And / or, the liquid nitrile rubber has a combined acrylonitrile content of 26-28%.
6. The nano silver paste as claimed in claim 1, characterized in that: The organic carrier is at least one of polyvinyl alcohol, polyvinyl butyral, paraffin and ethyl cellulose; And / or, the diluent is at least one of terpineol, ester alcohol, tributyl citrate and cyclohexylisoborneol.
7. The nano silver paste according to claim 1, characterized in that: The shear strength of the nano silver glue is greater than 55 MPa; And / or, the volume resistivity of the nano silver paste is 5×10 -6 ~6×10 -6 Ω·cm.
8. The method for preparing nano silver colloid according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. The resin, diluent, liquid nitrile rubber, organic carrier and composite silver filler are mixed according to the desired ratio to obtain a first mixture; S2. Add a defoaming agent to the first mixture, stir, and filter to obtain nano silver colloid.
9. The method for preparing nano silver colloid as claimed in claim 8, characterized in that: The mixing is carried out using a high-speed disperser, and the mixing speed is 1000-1500 rpm; And / or, the mixing time is 2 to 10 minutes; And / or, the mesh number of the filtration is 400-500 meshes.
10. The method for preparing nano silver colloid according to claim 8, characterized in that: Also included is a method for preparing a composite silver powder filler; The preparation method of the composite silver powder filler comprises the following steps: Step 1. crushing, grinding and sieving the copper-lanthanum alloy to obtain copper-lanthanum alloy powder; Step 2. Mix the copper-lanthanum alloy powder and the silver powder to obtain a composite silver powder filler.